2017
DOI: 10.1093/scan/nsx082
|View full text |Cite
|
Sign up to set email alerts
|

To err is (perfectly) human: behavioural and neural correlates of error processing and perfectionism

Abstract: The attitude towards one’s own imperfection strongly varies between individuals. Here, we investigated variations in error-related activity depending on two sub-traits of perfectionism, Personal Standard Perfectionism (PSP) and Evaluative Concern Perfectionism (ECP) in a large scale functional magnetic resonance imaging study (N = 75) using a digit-flanker task. Participants with higher PSP scores showed both more post-error slowing and more neural activity in the medial-frontal gyrus including anterior cingul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…After continued task repetition, control group performance declined to mirror that of the cocaine use group, suggesting that cocaine use group reaches the ‘fatigued’ level of cognitive control at a faster rate than controls (Moeller et al ., ). These findings also square with studies in healthy controls, which have reported that fMRI‐measured activation in the ACC extending into dorsomedial prefrontal cortex (PFC) tracks with PES (Hester et al ., ; Klein et al ., ; King et al ., ; Barke et al ., ). Other brain regions also may be implicated, however (Chevrier & Schachar, ; Zhang et al ., ), as impaired PES has been associated with hypofunctionality across multiple PFC regions (Kaufman et al ., ; Kopelman, ; Li et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…After continued task repetition, control group performance declined to mirror that of the cocaine use group, suggesting that cocaine use group reaches the ‘fatigued’ level of cognitive control at a faster rate than controls (Moeller et al ., ). These findings also square with studies in healthy controls, which have reported that fMRI‐measured activation in the ACC extending into dorsomedial prefrontal cortex (PFC) tracks with PES (Hester et al ., ; Klein et al ., ; King et al ., ; Barke et al ., ). Other brain regions also may be implicated, however (Chevrier & Schachar, ; Zhang et al ., ), as impaired PES has been associated with hypofunctionality across multiple PFC regions (Kaufman et al ., ; Kopelman, ; Li et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…In order to calculate post-error slowing (the amount a participant’s response time slows after an erroneous response [69]), we extracted the RT for every correct trial that was preceded by an error (i.e., post-error RT) and for every correct trial that was followed by an error (i.e., pre-error RT). Pre-error RT was then subtracted from post-error RT to get one value of post-error slowing (for methodology [69]). This was also done for correct trials that were preceded or followed by a correct trial (i.e., pre-correct RT subtracted from post-correct RT; see Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…These processes are grounded in the comparison of self to others as perfectionistic individuals frequently use comparison to evaluate performance and pursue high levels of achievement. Research has also indicated the MPFC becomes more activated when mistakes are made (Barke et al, 2017). Sensitivity to error making may lead to MPFC activation even in response to seemingly small mistakes among perfectionistic people.…”
Section: Medial Prefrontal Cortexmentioning
confidence: 99%
“…Because the DLPFC as a whole is implicated in self and emotional control (Hare et al, 2000;Lévesque et al, 2003), with the left DLPFC involved in task-shifting and right DLPFC involved in cognitive and emotional control, we predicted higher activation in perfectionistic participants who may implement greater cognitive control in order to regulate unpleasant emotions and avoid making mistakes. Because the MPFC is implicated in self-referential processing and perception of mistake making, we predicted the MPFC would show greater activation during error-prone behavioral tasks in the perfectionist group (Barke et al, 2017;Gusnard et al, 2001). Lastly, the potential involvement of the right IPL in self-other comparisons and relation to OCD and eating disorder severity suggests there might be greater activation in more perfectionist brains during tasks that result in greater errors as perfectionistic participants fail to meet high-task standards and engage in self-other comparisons (Feusner et al, 2008;Roth et al, 2007).…”
Section: Present Studymentioning
confidence: 99%
See 1 more Smart Citation